#### transgalactic

##### Banned

the telegan law basically states that the total sum of power is zero.

my prof proved lik this:

we choose a node (a point where more then one currents come together)

[latex][/latex]

and decide that the voltage on that node to be zero.

we designate the voltages on the nodes to be [latex]e_k[/latex]

[latex]J_k[/latex] is the current.

[latex]v_kJ_k=(e_a-e_b)J_{ab}[/latex]

[latex]v_kJ_k=\frac{1}{2}[(e_b-e_a)J_{ab}+(e_a-e_b)J_{ab}][/latex]

[latex]n_t[/latex] is the number of nodes.[/latex]

[latex]B[/latex] is the number of branches.[/latex]

[latex]\sum_{k}^{B}v_kJ_k=\frac{1}{2}\sum_{a=1}^{n_t}\sum_{b=1}^{n_t}(e_a-e_b)J_{ab}[/latex]

each J that does not exist in the graph will be zero.

[latex]\sum_{k}^{B}v_kJ_k=\frac{1}{2}\sum_{a=1}^{n_t}e_a\sum_{b=1}^{n_t}J_{ab}-\frac{1}{2}\sum_{a=1}^{n_t}e_b\sum_{b=1}^{n_t}J_{ab}=0[/latex]

because by kcl

[latex]\sum_{b=1}^{n_t}J_{ab}=0[/latex]

my problem iswhen he sums for all nodes

he uses

[latex]\sum\sum[/latex] sign which by me represents multiplication

of the sums

why not [latex]\sum+\sum[/latex],thus we can know that ist the sum of many similar equations.

but how he did it doesnt represent a sum

my prof proved lik this:

we choose a node (a point where more then one currents come together)

[latex][/latex]

and decide that the voltage on that node to be zero.

we designate the voltages on the nodes to be [latex]e_k[/latex]

[latex]J_k[/latex] is the current.

[latex]v_kJ_k=(e_a-e_b)J_{ab}[/latex]

[latex]v_kJ_k=\frac{1}{2}[(e_b-e_a)J_{ab}+(e_a-e_b)J_{ab}][/latex]

[latex]n_t[/latex] is the number of nodes.[/latex]

[latex]B[/latex] is the number of branches.[/latex]

[latex]\sum_{k}^{B}v_kJ_k=\frac{1}{2}\sum_{a=1}^{n_t}\sum_{b=1}^{n_t}(e_a-e_b)J_{ab}[/latex]

each J that does not exist in the graph will be zero.

[latex]\sum_{k}^{B}v_kJ_k=\frac{1}{2}\sum_{a=1}^{n_t}e_a\sum_{b=1}^{n_t}J_{ab}-\frac{1}{2}\sum_{a=1}^{n_t}e_b\sum_{b=1}^{n_t}J_{ab}=0[/latex]

because by kcl

[latex]\sum_{b=1}^{n_t}J_{ab}=0[/latex]

my problem iswhen he sums for all nodes

he uses

[latex]\sum\sum[/latex] sign which by me represents multiplication

of the sums

why not [latex]\sum+\sum[/latex],thus we can know that ist the sum of many similar equations.

but how he did it doesnt represent a sum

Last edited: